Social media interactive advertising and purchase intention of the UAE customers: an empirical analysis - Mohammed Fathi Yousaf,; Koo, Ah Choo; Mohd Hafizuddin Mohd Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The advent of social media technologies, specifically the phenomenal growth of online and interactive advertising, has assisted various organizations in responding to and communicating with respective consumers at sustainable expenditures through various online channels, including social media, with immense potential and popularity levels. Limited studies have been conducted to examine the connection between consumer engagements by small and medium enterprises (SMEs) and their respective promotional performances, as consumer purchase intention would be notably affected by the ability of an enterprise to interact and share information. Therefore, the current study aims to evaluate the impacts of attitude, brand loyalty, brand image, and brand awareness on interactive advertising and engagement with consumers via social media in the United Arab Emirates (UAE) to promote SME digital lifestyle products. Accordingly, a quantitative survey was administered to evaluate 308 responses from customers of companies vending digital lifestyle products before conducting partial least square structural equation modeling (PLS-SEM) to analyze the collected data. The results demonstrated significant positive relationships between both brand loyalty and brand awareness and consumer purchase intention, respectively, whereas the relationships between attitude and brand image and consumer purchase intention were separately discovered to be insignificant.